The Role of Santri in Election Law Enforcement (Case Study of Money Political Practices in Demak District Election) - Fitriyani, Fitriyani (Law Research Review Quarterly, 2018)
The practice of money politics is a major obstacle in enforcing the Pilkades law in Demak district. The practice of money politics is a threat to the country's security. The main contributing factor is the cultural factor which is wrong about democratic principles. The government has tried to give strict sanctions in eradicating political practices in Indonesia. But the problem is, in the implementation of the Demak Pilkades, the Demak district government has not yet given decisive action. This study aims to find new solutions in enforcing the Demak district election law. This study uses a non-doctrinal approach. Based on the results of the analysis that Demak Pilkades money politics practice is one of the extraordinary legal problems, the solution must be in an extraordinary way (rule breaking) which involves the role of santri in the pesantren including the role of the kiai / religious teacher. There are two ways: first, it involves 3,691 kiai / ustadz to influence and provide understanding of violations of money politics practices to the people in Demak district. Considering, in Demak district, the kiai is considered a leader figure who has an important role in determining which attitudes and steps will be taken by the local community to make decisions or policies. This step will have a direct impact in eradicating the practice of money politics. Second, involving the role of students directly.